Combining Polymerization and Templating toward Hyper-Cross-Linked Poly(propargyl aldehyde)s and Poly(propargyl alcohol)s for Reversible H2O and CO2 Capture and Construction of Porous Chiral Networks - Havelková, Lucie; Bashta, Bogdana; Hašková, Alena; Vagenknechtová, Alice; Vyskočilová, Eliška; Brus, Jiří; Sedláček, Jan (Polymers, 2023)
Two series of hyper-cross-linked microporous polyacetylene networks containing either -[CH=C(CH=O)]- or -[CH=C(CH2OH)]- monomeric units are reported. Networks are prepared by chain-growth copolymerization of acetal-protected propargyl aldehyde and acetal-protected propargyl alcohol with a 1,3,5-triethynylbenzene cross-linker followed by hydrolytic deprotection/detemplating. Deprotection not only liberates reactive CH=O and CH2OH groups in the networks but also modifies the texture of the networks towards higher microporosity and higher specific surface area. The final networks with CH=O and CH2OH groups attached directly to the polyene main chains of the networks have a specific surface area from 400 to 800 m2/g and contain functional groups in a high amount, up to 9.6 mmol/g. The CH=O and CH2OH groups in the networks serve as active centres for the reversible capture of CO2 and water vapour. The water vapour capture capacities of the networks (up to 445 mg/g at 297 K) are among the highest values reported for porous polymers, making these materials promising for cyclic water harvesting from the air. Covalent modification of the networks with (R)-(+)-3-aminopyrrolidine and (S)-(+)-2-methylbutyric acid enables the preparation of porous chiral networks and shows networks with CH=O and CH2OH groups as reactive supports suitable for the anchoring of various functional molecules.
Keywords: chiral modification; hyper-cross-linked; polyacetylenes; porous polymers; water harvesting